2007
DOI: 10.1080/00423110601059013
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of transient slosh within a partly-filled tank equipped with baffles

Abstract: The directional dynamic analyses of partly-filled tank vehicles have been limited to quasi-static fluid motion due to computational complexities associated with dynamic fluid slosh analyses. The dynamic fluid slosh causes significantly higher magnitudes of slosh forces and moments in the transient state that cannot be characterized through quasi-static approach, which provides reasonably good estimates of the mean responses. In this study, a three-dimensional nonlinear model of a partly-filled cylindrical tank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 12 publications
2
36
0
Order By: Relevance
“…A quasi-static slosh model, however, is limited to fluid slosh in the steady state, and cannot be applied to study effects of baffles, particularly the forces and moments arising from the transient slosh. Moreover, the fundamental slosh frequencies in a full size cleanbore tank occur in the 0.16-0.26 Hz range in the longitudinal mode, and in 0.56-0.74 Hz in the lateral mode, depending upon the fill volume and tank size [6,[8][9][10]. These frequencies may lie in the vicinity of the steering frequency and the rotational modes of the sprung mass, and could lead to resonant oscillations.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A quasi-static slosh model, however, is limited to fluid slosh in the steady state, and cannot be applied to study effects of baffles, particularly the forces and moments arising from the transient slosh. Moreover, the fundamental slosh frequencies in a full size cleanbore tank occur in the 0.16-0.26 Hz range in the longitudinal mode, and in 0.56-0.74 Hz in the lateral mode, depending upon the fill volume and tank size [6,[8][9][10]. These frequencies may lie in the vicinity of the steering frequency and the rotational modes of the sprung mass, and could lead to resonant oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The tank trucks generally employ transverse baffles with a large central orifice and a nearly semi-circular equalizer opening at the bottom. The effects of such baffles on the longitudinal and lateral fluid slosh have been investigated in only a few experimental and analytical studies [4,6,[18][19][20][21]. These have shown that presence of transverse baffles could limit slosh only in the longitudinal direction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations